HCV cure for everyone or which challenges remain? - Jürgen Kurt Rockstroh (Elsevier, 2015)
Following the approval of the first HCV direct-acting antiviral (DAA) in 2011, an unforeseen revolution in the treatment of chronic hepatitis C has taken place. In 2015 several all-oral DAA regimens, combining agents from different families (NS5B nucleotide inhibitors, NS5B non-nucleoside inhibitors, NS5A replication complex inhibitors and NS3/4A protease inhibitors) are now commercially available. In clinical trials, these regimens result in an increase in sustained virological response (SVR) rates to above 90-95% and reduce the duration of treatment to 12 weeks or less. As these new all-oral therapies are easy to take, with some already available as simple fixed-dose combinations, and are associated with minimal adverse events, increasing numbers of HCV patients appear treatable with these modern regimens. Nevertheless, the questions remain on how far the spectacular treatment trial results can be reproduced in clinical practice and whether more challenging patient populations, including previous non-responders and patients with advanced cirrhosis, will continue to exist even in the era of all-oral DAA therapy.